(untitled) (مجلة إحالات, 2026)
The presence of literary readings is characterized by strength and intensity in Jacques Derrida’s ambiguous philosophy, as it relies on allegorical, graphic, and metaphorical methods in undermining the constants of philosophical saying and gnawing at its essence, so that deconstruction opens up to the dual agreement between contradictions and opposites, in advance a perpetually attentive reading that leads the meaning to the extremes of contemplative silence and interpretive giving. Through this article, we will discuss how Derrida re-posed the question of the philosophical reading of literature, and how he presented a literary reading with philosophical eyes. And how deconstruction shook the image of the text by raising critical questions about borders, boundaries, edges, and margins.